Analyzing The Effect of Human Capital Drivers on Company Performance Through Employees Perspective Case Study: LKBN PERUM ANTARA - Zakaria, Adyssa Riska Larasati; Welly, John (The Indonesian Journal of Business Administration, 2015)
Abstract. In Indonesia, the rapid growth of media industry has become undisputed fact all over the last ten years. The researcher conducted this research to get deeper insights that focused on organizational condition in ANTARA, one of the leading news agency in Indonesia, particularly about its human resource practices in order to increase the companyâ€™s performance. The research objective is to capture and identify human capital practices using a self-developed survey based on SHRM Foundation Effective Practice Guidelines Series titled â€œHuman Resource Strategy: Adapting to The Age of Globalizationâ€ by Patrick M. Wright and the human capital measurement tool developed by Laurie Bassi and Daniel McMurrer. The survey was spread to employees that work in ANTARA offices in Jakarta during August to October 2014.The results of this research shows that ANTARA still needs to do some effort in order to maintain and develop their performance by improving their human capital practices, particularly to focus in increasing their employee engagement, knowledge accessibility, workforce optimization, and learning capacity.Keywords: human capital, assessment tool, company performance, employee perspective, news agency